Visual outcome of conventional extra-capsular cataract extraction with posterior chamber intraocular lens implantation versus manual small incision cataract surgery - Sharma, A; Lavaju, P (Nepalese Journal of Ophthalmology, 2010)
DOI: 10.3126/nepjoph.v1i2.3694 Nep J Oph 2009;1(2):151